Estrategias Metodológicas en el proceso de enseñanza aprendizaje de los niños de 5 años de la Escuela Particular “Ciudad de Yantzaza” 2023-2024. - Calva González, Yuri Giomara (2024)
The objective of this curricular integration project was to analyze the methodological strategies and their influence on the teaching-learning process in 5-year-old children at "Ciudad de Yantzaza" Private Basic Education School; it was a non-experimental, cross-sectional study with a qualitative approach. An observation sheet consisting of 6 items and a 6 questions interview to the teacher were applied as instruments. The result of the teacher survey was verified through the observation sheet, with a sample of 16 girls and boys from the preparatory class and 2 teachers. The results were reflected in a triangulation table divided by two variables: methodological strategies and teaching-learning; which guarantees the validity and reliability of the obtained information. According to the results obtained, it was evident that within the variable of methodological strategies, 4 interview and observation questions were applied. It was determined that the teacher uses psychomotor play for coordination and body expression activities, and symbolic play for thematic roles. The observation shows that she always uses symbolic gaming, didactic, and traditional games, almost always psychomotor games, but never dramatization. Within the second variable of teaching-learning, 2 interview and observation questions were applied; it was determined that the teacher evaluates through observation, almost always using games and always workshops, but never corners or puppets. She promotes respect, emotion management, and motivation; creating a trust environment for the children. In conclusion, a discrepancy was observed between the mentioned methodological strategies and those implemented by the teacher, highlighting the need to implement strategies to optimize skill development in 5-year-old children. Key words: child development, corners, puppets, meaningful learning.